THE ECONOMICS OF LAND MAFIA: SPECULATION, MARKET DISTORTION, AND POLICY IMPLICATIONS - Gunawan Widjaja (Adisam Publisher, 2025)
This study examines the economic dynamics of land mafia, focusing on speculation practices, market distortions, and relevant policy implications in the context of land management in Indonesia. Land mafia uses various modus operandi to illegally control and trade land, causing disproportionate increases in land prices and market failures in the form of monopolies and manipulation. This condition narrows public access to land ownership and exacerbates socio-economic inequality. The research method used was a literature review, which examined various literature, case reports, and existing policies to obtain a comprehensive understanding of the speculation and market distortion caused by the land mafia and to assess the effectiveness of the policies implemented. The results of the study emphasise the need for integrated and digitally-based land management reform, strengthened law enforcement, and community participation in land market supervision. A holistic and inclusive policy approach is urgently needed so that the land market can function fairly and support sustainable development. This study provides recommendations for policymakers to improve transparency, accountability, and effectiveness of land market regulation in order to suppress land mafia practices.